Maqāṣidi Tafsir: Uncovering and Presenting Maqāṣid Ilāhī-Qur’anī into Contemporary Context - Aksin Wijaya; Shofiyullah Muzammil (Al-Jami'ah: Journal of Islamic Studies, 2021)
This writing discusses maqāṣidi tafsīr (the interpretation that represents God’s intention). It endeavors to answer three questions: Firstly, what are models of maqāṣidi tafsīr that are in circulation? Secondly, what are their strengths and weaknesses? Thirdly, what are the true forms of maqāṣidi tafsīr? Historical approach is employed to answer the first question, whereas critical hermeneutics and philosophy are used to discussed the second and third questions. Using the intellectual history, the process of the formation of maqāṣidi tafsīr will be discovered; critical hermeneutics will uncover its strengths and weaknesses; and new frameworks will be formulated for contemporary contexts using philosophical hermeneutics. It is expected from this writing that maqāṣidi tafsīr will remain theologically, epistemologically and hermeneutically well-established so that it will be considered as one of alternative approaches in the Quranic studies. Three conclusions are drawn from this writing: firstly, maqāṣidi tafsīr is in the process of becoming a theory for studying the Qur’an. Secondly, maqāṣidi tafsīr does have strength and weaknesses. It originates from Islamic tradition, and becomes a kind of alternative-moderate between two extreme tafsīrs: textual and liberal-substantialist. Still, it is not yet well-established in term of theology, epistemology and hermeneutics. Third, maqāṣidi tafsīr combines three approaches in locating what God wants in the Quran, because it is not only textual, ideal-moral, but also spiritual-substantial. [Artikel ini membahas tafsir maqāṣid dengan menjawab tiga pertanyaan yaitu seperti apa model tafsir maqāṣid yang beredar saat ini, apa kelemahan dan kelebihan dari model tersebut, dan bagaimana bentuk tafsir maqāṣid yang sebenarnya. Pertanyaan pertama dijelaskan menggunakan pendekatan sejarah dan pertanyaan kedua dan ketiga dijelaskan menggunakan pendekatan hermeneutika kritis dan filosofis. Sejarah intelektual digunakan untuk menelusuri proses pembentukan tafsir maqāṣid sedangkan hermenuetika kritis digunakan untuk menilai kekuatan dan kelemahan serta hermeneutika filosofis untuk mereformulasi kerangka baru sesuai konteks kontemporer. Artikel ini mencoba meyakinkan secara teologis, epistemologis, dan hermeneutis bahwa tafsir maqāṣid akan semakin mapan dan bisa menjadi alternatif pendekatan dalan studi Qur’an. Tiga kesimpulan dalam artikel ini adalah pertama, tafsir maqāṣid sedang berproses menjadi sebuah teori dalam studi Qur’an. Kedua,meski mempunyai kelebihan dan kekurangan, pendekatan ini bisa menjadi alternatif moderat antara tafsir tektual dan liberal-subtansialis. Terakhir, pendekatan ini menggunakan tiga kerangka pikir dalam memahami maksud Tuhan dalam Qur’an, teks, ideal moral dan juga spiritual substansial.]